Dynamic expressions - Graham, Michele S., author; Twarogowski, Leroy A., advisor; Dormer, James T., committee member; Simons, Stephen R., committee member; Orman, Jack L., committee member; Bowman, J. P., committee member (Colorado State University. Libraries, 2004)
To view the abstract, please see the full text of the document.
Keywords: Intaglio printing